2015
DOI: 10.1002/anie.201409691
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing Mechanochemical Bond Rupture by Embedding the Mechanophore into a Macrocycle

Abstract: Mechanophores contain a mechanically labile bond that can be broken by an external mechanical force. Quantitative measurement and control of the applied force is possible through atomic force microscopy (AFM). A macrocycle was synthesized that contains both the mechanophore and an aliphatic chain that acts as a "safety line" upon bond breaking. This ring-opening mechanophore unit is linked to poly(ethylene glycol) spacers, which allow investigation by single molecule force spectroscopy. The length increase upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 48 publications
5
58
0
2
Order By: Relevance
“…These parameters (Figure S1 and Tables S1, S2 in the Supporting Information) were subsequently used in as tandard Arrhenius-type model to describe the thermally activated and mechanically assisted bond rupture process.A pplying bond rupture probability theory,t he most probable rupture forces were calculated as afunction of the externally applied force for ag iven loading rate.T om imic the conditions used in ultrasound polymer mechanochemistry, [18] al oading rate of 10 8 nN s À1 was used (see the Supporting Information for details). In contrast, the triazoles 1s, 3s,and 5s rupture at forces F s(I) > 7nN, as can be seen when pulling on the internal anchor atoms.F or 1s, 3s, and 5s,l inker rupture is significantly more likely (F 1s(T) = 4.09 nN;F 3s(T) = 4.96 nN;F 5s(T) = 5.01 nN) and cycloreversion appears experimentally impossible.T his result is in line with previous DFT simulations [5] and single-molecule force spectroscopy experiments of 1s, [12] which suggest that mechan- In contrast, the triazoles 1s, 3s,and 5s rupture at forces F s(I) > 7nN, as can be seen when pulling on the internal anchor atoms.F or 1s, 3s, and 5s,l inker rupture is significantly more likely (F 1s(T) = 4.09 nN;F 3s(T) = 4.96 nN;F 5s(T) = 5.01 nN) and cycloreversion appears experimentally impossible.T his result is in line with previous DFT simulations [5] and single-molecule force spectroscopy experiments of 1s, [12] which suggest that mechan- …”
supporting
confidence: 89%
“…These parameters (Figure S1 and Tables S1, S2 in the Supporting Information) were subsequently used in as tandard Arrhenius-type model to describe the thermally activated and mechanically assisted bond rupture process.A pplying bond rupture probability theory,t he most probable rupture forces were calculated as afunction of the externally applied force for ag iven loading rate.T om imic the conditions used in ultrasound polymer mechanochemistry, [18] al oading rate of 10 8 nN s À1 was used (see the Supporting Information for details). In contrast, the triazoles 1s, 3s,and 5s rupture at forces F s(I) > 7nN, as can be seen when pulling on the internal anchor atoms.F or 1s, 3s, and 5s,l inker rupture is significantly more likely (F 1s(T) = 4.09 nN;F 3s(T) = 4.96 nN;F 5s(T) = 5.01 nN) and cycloreversion appears experimentally impossible.T his result is in line with previous DFT simulations [5] and single-molecule force spectroscopy experiments of 1s, [12] which suggest that mechan- In contrast, the triazoles 1s, 3s,and 5s rupture at forces F s(I) > 7nN, as can be seen when pulling on the internal anchor atoms.F or 1s, 3s, and 5s,l inker rupture is significantly more likely (F 1s(T) = 4.09 nN;F 3s(T) = 4.96 nN;F 5s(T) = 5.01 nN) and cycloreversion appears experimentally impossible.T his result is in line with previous DFT simulations [5] and single-molecule force spectroscopy experiments of 1s, [12] which suggest that mechan- …”
supporting
confidence: 89%
“…This conclusion is corroborated by independent calculations [17,18] where,m oreover,i th as been shown that simple CÀCb ond rupture [17] in the force-transducing chains attached to the mechanophore becomes energetically preferred over cycloreversion even at about 1nN. Furthermore,r ecent singlemolecule force spectroscopy experiments "cannot determine whether it was really mechanochemicallyi nduced retro-click reactions of the 1,2,3-triazole ring that took place or merely bond rupture next to it" [19] ,which leaves the case open.…”
mentioning
confidence: 91%
“…A follow‐up paper by a different research group using an atomic force microscope (AFM) single molecule force spectroscopy technique suggested that the chance for selective triazole rupture in the presence of C−Si bond is low. In several thousands of events, only three showed potential triazole rupture, but there was no suitable method to differentiate triazole rupture from other bond rupture . Earlier density functional theory calculation indicated force‐induced selective triazole rupture is unlikely .…”
Section: Introductionmentioning
confidence: 99%